Recombination, Pairing, and Synapsis of Homologs during Meiosis - Zickler, Denise (Cold Spring Harb Perspect Biol, 2015)
Recombination is a prominent feature of meiosis in which it plays an important role in increasing genetic diversity during inheritance. Additionally, in most organisms, recombination also plays mechanical roles in chromosomal processes, most notably to mediate pairing of homologous chromosomes during prophase and, ultimately, to ensure regular segregation of homologous chromosomes when they separate at the first meiotic division. Recombinational interactions are also subject to important spatial patterning at both early and late stages. Recombination-mediated processes occur in physical and functional linkage with meiotic axial chromosome structure, with interplay in both directions, before, during, and after formation and dissolution of the synaptonemal complex (SC), a highly conserved meiosis-specific structure that links homolog axes along their lengths. These diverse processes also are integrated with recombination-independent interactions between homologous chromosomes, nonhomology-based chromosome couplings/clusterings, and diverse types of chromosome movement. This review provides an overview of these diverse processes and their interrelationships.